Sifat Fisik Beton Dengan Bahan Tambah Bakteri Bacillus Subtilis Pada Lingkungan Sulfat - Kurnia Desmilestari; Zulfikar Djauhari; Enno Yuniarto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Concrete is a common material used in structures, such as foundations, roads, and bridges. Concrete has a high compressive strength, but the tensile strength of the concrete is low. At the time the tensile strength limit of concrete is reached, the crack will exist on the tension side of the concrete. The use of bacteria as an added ingredient in concrete is an innovation to reduce the crack. According to Pangeran and Karolina’s research (2017), the addition of bacteria to the concrete can also increase the compressive strength of the concrete. In this research, a 25 ml of Bacillus subtilis solution with the concentration of 105 CFU/ml were added to a concrete mixture. The concrete was soaked in normal water and sulfate solution with the concentration of 150 ppm and the physical properties were examined such as workability, porosity, and shrinkage. There were 3 variations in the specimens, namely normal concrete (BN), bacterial concrete (BB), and bacterial concrete soaked in sulfate solution (BBS). Theresults of this study indicated that slump on specimen BBS was 8.05% and 18.98% higher than specimen BN and BB, respectively. The porosity on specimen BBS was 11.07% and 14.47% higher than specimen BN and BB, respectively. Lastly, the shrinkage on specimen BBS was 1.42% and 18.54% higher than specimen BN and BB, respectively. So it can be concluded that bacteria does have a good effect on the physical properties and soaking the bacterial concrete on the sulfate can adversely affect the physical properties of concrete.Keywords : concrete, bacillus subtilis bacteria, sulfate, physical properties